Associated Injuries in Ankle Fractures Involving the Tillaux-Chaput Fragment in Adults - Jafet Massri-Pugin MD; Gabriel Matamoros MD; Sergio Morales MD, MSc; María Jesús Lira MSc; Jorge Filippi MD, MBA (Foot & Ankle Orthopaedics)
Category: Trauma; Ankle Introduction/Purpose: Tillaux-Chaput fractures (TCF) consist of fractures of the anterolateral distal tibia. They are considered a rare entity during adulthood and can occur in isolation or be associated with other injuries around the ankle. When the TCF is ignored, there is a risk of complications such as chronic pain, instability, and post-traumatic ankle osteoarthritis. Although prior studies have correlated some factors with the presence of TCF, to our knowledge, no studies have evaluated which variables are independently associated with the presence of TCF in a multivariate regression analysis. This study aimed to identify which factors are related to the presence of TCF in ankle injuries. Methods: A retrospective review of ankle fractures evaluated in the emergency or outpatient department between 2013-2023 at a single trauma center was performed. Inclusion criteria were age≥18 years, ankle radiographs and CT scan evaluation, and the presence of TCF confirmed by CT scan. Exclusion criteria were pilon/distal tibial fractures, or prior ankle surgery. A radiologist classified the TCF into: type 1,extraarticular avulsion; type 2,fracture with involvement of the incisura; and type 3, fracture with impaction of the anterolateral plafond. A matching 1:2 was performed among ankle fractures with and without TCF. The following variables were collected: sex, age(< 50 vs >50 years), dislocation, Weber classification, Maisonneuve fracture, type of medial malleolar fracture(Herscovici classification), type of posterior malleolar fracture (Bartonicek/Rammelt classification), Lauge-Hansen classification, type of malleolus involved, and acute osteochondral lesion of the talus. Logistic regression was performed to detect which variables had association with the TCF and their subtypes.P-value< 0.05 was considered significant. Results: 1134 ankle fractures were evaluated, of which 481 fulfilled the eligibility criteria. Eighty-three (17.3%) ankle fractures had a TCF, of which 37(44.6%) were type I, 37(44.6%) type 2, and 9(9.6%) type 3. In patients with TCF, the mean age was 52.2(19.7) years, and 55(66.3%) were women. Six(7.2%) patients had an isolated TCF. Fifty-six(67.5%), 50(60.2%), and 62 (74.7%) ankles had involvement of the lateral, medial, and posterior malleolus, respectively. Eight (9.6%) ankles had a Maisonneuve fracture. In the multivariate-regression analysis, the patients aged>50 years (OR=2.73,95%CI 1.45-5.14) and Lauge-Hansen/pronation external rotation injuries (OR=2.94,95%CI 1.43-6.06) had a significant association with the TCF. When analyzing for subtypes, the ankle dislocation (OR=3.16,95%CI 1.11-8.96), and the absence of posterior malleolar fracture (OR=5.97,95%CI 1.65-21.6) were associated with TCF type 2 and 3. Conclusion: Patients aged >50 years and pronation external rotation injuries were the unique independent variables associated with the existence of a TCF in this study. Furthermore, ankle dislocation and the indemnity of the posterior malleolus increased the chance of having a more severe TCF by 3.2 and 6.0 times, respectively. This study provides novel insights into the factors associated with TCF and its subtypes during adulthood, allowing for a higher degree of suspicion during the ankle fracture evaluation.